(untitled) (Journal of the College of Basic Education, 2022)
Thought in general, and deconstruction in particular, plays an important role and a direct influence on the movement of arts, including the plastic arts. It has a vital role in the plastic creative process, especially in the art of sculpture. . And that is in his relentless pursuit to achieve the new structure or structures in sculpture by performing a new formation that diversifies according to the levels of the sculptor’s response to scientific progress and the technological revolution and the investment of its scrap, or according to the sculptor’s expression of his anxious changing psychology searching for the new, the unique and the strange, or through the artist’s attempts to embody the innovative feature in sculpture.